The Customization of Science: The Impact of Religious and Political Worldviews on Contemporary Science - Fuller, Steve; Stenmark, Mikael; Zackariasson, Ulf (Palgrave Macmillan, 2020)
This collection explores whether and how religious and secular worldviews and political ideologies held by scientists, citizens, decision-makers and politicians influence science as practiced and understood today. Contributors explore the social and scientific repercussions of 'customizing' science to fit the needs and interests of various groups